Warm-Up With Added Respiratory Dead Space Volume Mask Improves the Performance of the Cycling Sprint Interval Exercise: Cross-Over Study - Danek, Natalia; Michalik, Kamil; Zatoń, Marek (Frontiers in Physiology, 2022)
Special breathing exercises performed during warm-up lead to hypercapnia and stimulation of mechanisms leading to increased exercise performance, but the effect of a device that increases the respiratory dead space volume (ARDSv) during warm-up has not been studied. The purpose of this study was to investigate the effect of 10 minutes warm up with ARDSv on performance, physiological and biochemical responses during sprint interval cycling exercise (SIE). During four laboratory visits at least 72 hours apart, they completed: 1) a incremental exercise test on a cycloergometer, 2) a familiarization session, and cross-over SIE sessions conducted in random order on visits 3) and 4). During one of them, 1200 mL of ARDSv was used for breathing over a 10-minute warm-up. SIE consisted of 6 x 10-s all-out bouts with 4-min active recovery. Work capacity, cardiopulmonary parameters, body temperature, respiratory muscle strength, blood acid-base balance, lactate concentration, and rating of perceived exertion were analyzed. After warm-up with ARDSv, PETCO2 was 45.0 ± 3.7 vs. 41.6 ± 2.5 (mm Hg) (p<0.001). Body temperature was 0.6 (°C) higher after this form of warm-up (p<0.04), bicarbonate concentration increased by 1.8 (mmol.l-1) (p<0.01). As a result, work performed was 2.9% greater (p<0.01) compared to the control condition. Respiratory muscle strength did not decreased. Warming up with added respiratory dead space volume mask prior to cycling SIE produces an ergogenic effect by increasing body temperature and buffering capacity.